Legal contrivances in Islamic legal texts: their classification and relevance to transactional expressions - Sadique, Muhammad Abdurrahman (Zes Rokman Resources, 2023)
Reference to what could be considered as legal contrivances appears in some prophetic traditions, in addition to some verses of the Qur’an. Although some early jurists such as Imam Malik are considered to have held all contrivances impermissible, which approach has also been adopted by Imam Ahmad and his followers of the initial centuries, the majority of jurists have refrained from condemning all applications falling under them in general as unlawful. In dividing legal contrivances into permissible and impermissible varieties, many of the jurists have fundamentally taken the outcome into consideration. It is observed that the difference on the validity or otherwise of legal contrivances, especially in the domain of transactions, could be traced to the fundamental difference on the basis of contracts with regard to the wording of a contract and its meaning or intent. It is noted that a section of jurists have also taken into consideration the time a contrivance is employed in certain transactions with regard to rights that may be affected, in determining the acceptability of the contrivance.